2013
DOI: 10.1371/journal.pone.0084361
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Persister Cells Formation in Acinetobacter baumannii

Abstract: Bacterial persistence is a feature that allows susceptible bacteria to survive extreme concentrations of antibiotics and it has been verified in a number of species, such as Escherichia coli, Pseudomonas aeruginosa, Staphylococcus spp., Mycobacterium spp. However, even though Acinetobacter baumannii is an important nosocomial pathogen, data regarding its persistence phenotype are still lacking. Therefore, the aim of this study was to evaluate the persistence phenotype in A. baumannii strains, as well as its va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 25 publications
(36 reference statements)
3
46
0
Order By: Relevance
“…Furthermore, we observed that combining the highest doses tested of both antimicrobials was more efficient even after 6 h exposure, and rapidly reduced the bulk of cells in comparison with the other combinations. Thus, taking into account the present data and our previous findings that polymyxin B (15 µg ml À1 ) [8] or meropenem alone (15, 30, 100 and 200 µg ml À1 ) were not able to eradicate A. baumannii persisters [13], we may highlight that there is a synergistic bactericidal effect of this drug combination. Simultaneous treatment employing high doses of conventional antimicrobials has also been reported as being able to completely eradicate Staphylococcus aureus persister cells within a few hours of antibiotic combination exposure [14].…”
Section: Combination Of Polymyxin B and Meropenem Eradicates Persistesupporting
confidence: 71%
See 2 more Smart Citations
“…Furthermore, we observed that combining the highest doses tested of both antimicrobials was more efficient even after 6 h exposure, and rapidly reduced the bulk of cells in comparison with the other combinations. Thus, taking into account the present data and our previous findings that polymyxin B (15 µg ml À1 ) [8] or meropenem alone (15, 30, 100 and 200 µg ml À1 ) were not able to eradicate A. baumannii persisters [13], we may highlight that there is a synergistic bactericidal effect of this drug combination. Simultaneous treatment employing high doses of conventional antimicrobials has also been reported as being able to completely eradicate Staphylococcus aureus persister cells within a few hours of antibiotic combination exposure [14].…”
Section: Combination Of Polymyxin B and Meropenem Eradicates Persistesupporting
confidence: 71%
“…Nevertheless, antimicrobial therapy failure has been reported, especially in recalcitrance of chronic infections, which may be due to the tolerance mediated by persister cells [5,6] -a microbial subpopulation able to survive to normally lethal concentrations of bactericidal antimicrobials [7], as has been previously described in Acinetobacter spp. exposed to polymyxin B [8]. This tolerance appears to be a transient phenotype that may be understood as arising from a combination of epigenetic inheritance and cellular noise [9], whose regulation involves a multiplicity of pathways [10].…”
Section: Combination Of Polymyxin B and Meropenem Eradicates Persistementioning
confidence: 99%
See 1 more Smart Citation
“…cinetobacter baumannii is an emerging opportunistic human pathogen that causes a plethora of nosocomial infections (1). The ability of this pathogen to sense and react to environmental and host stress signals allows it to persist in medical settings and in human hosts (2).…”
mentioning
confidence: 99%
“…The sensitivity of bacteria with slow growth in the membrane decreases and enters into the "hibernation" state. [21] Until the drug stops functioning, residual bacteria quickly multiplies to form a new biofilm by use of dead ones as a nutrient source, which stimulates the recurrence of infection. In addition, there is also significant different in pH value between inside and outside of biofilm, mainly due to the accumulation of acidic metabolites to reduce drug sensitivity.…”
Section: Change Of Living Environment In Biofilmmentioning
confidence: 99%